The Effect of Toric Intraocular Lens Implantation in Irregular Corneal Steep and Flat Meridian - Ho Sik Hwang (Hindawi Limited, 2021)
Purpose. To evaluate the effect of toric intraocular lens implantation in cataract patients with irregular corneal steep and flat meridian. Methods. Data of 112 eyes of 78 patients who underwent toric intraocular lens implantation were analyzed retrospectively. Steep meridian deviations (not 180°) and steep and flat meridian deviations (not 90°) were classified as 0, 1–9, 10–19, 20–29, 30–39, and over 30°. Meridian deviation was measured with a sagittal map of a rotating Scheimpflug camera (Pentacam®: Oculus, Wetzlar, Germany) using PicPickTools (NGWIN, Seoul, Korea). Results. Residual astigmatism (D) of 0 (0.51 ± 0.13, 0.55 ± 0.15) and 1–9 (0.61 ± 0.16, 0.66 ± 0.19) groups were significantly lower than that of 10–19 (0.92 ± 0.24, 0.90 ± 0.28), 20–29 (0.10 ± 0.32, 1.01 ± 0.35), and over 30° groups (1.12 ± 0.37, 1.14 ± 0.40) both in steep meridian deviations and horizontal and vertical meridian deviations at 6 months (P<0.05). Postoperative mean UCVA (logMAR) of 0 (0.09 ± 0.04, 0.09 ± 0.05) (logMAR) and 1–9 (0.10 ± 0.04, 0.11 ± 0.08) groups was significantly improved compared to that of 10–19 (0.14 ± 0.05, 0.17 ± 0.10), 20–29 (0.18 ± 0.08, 0.21 ± 0.10), and over 30° groups (0.20 ± 0.09, 0.22 ± 0.11) both in steep meridian deviations and horizontal and vertical meridian deviations at 6 months (P<0.05). Conclusions. Correction of astigmatism with toric intraocular lens implantation is not accurate in corneas with steep meridian deviations and steep and flat meridian deviations of more than 10°. Therefore, care should be taken when we perform toric intraocular lens implantation in patients with irregular corneal meridian.